Description of the Impact of Divorce on the Psychic Condition of Children - Ismail, Budi (Journal of Asian-african Focus in Health, 2023)
This study aims to determine how the psychological description of children and parents who experience divorce. This study uses a phenomenological approach using qualitative descriptive methods, namely data collection through interviews. The subjects in this study were 4 children whose parents were divorced. From the research results, it was found that parental divorce has an impact on several aspects of child development, namely 1) psychological aspects, 2) cognitive aspects, 3) social aspects, 4) moral aspects, 5) emotional aspects 6) personality, and 7) religion. These aspects are influenced by the social support that children get.